2017
DOI: 10.1108/rbf-06-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Managerial decision horizon and real estate investment trusts (REITs)

Abstract: Purpose The purpose of this paper is to examine the effects of managerial decision horizon (MDH) on real estate investment trust (REIT) behavior and performance. Design/methodology/approach In this study, the authors expand the number of proxies and measure managerial horizon by CEO age, CEO tenure, cash compensation relative to total compensation, and the amount of vested equity-based compensation to total compensation. To avoid potential measurement error, the authors compute the average ranking score of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…One of the most common scope ofstudies in REITs performance is comparing performance of one or some REITs companies within one jurisdiction (Akinsomi, Ong, Ibrahim, & Newell, 2016;Aro-gordon, 2015;Asteriou & Beigazi, 2013;Bene, Anderson, & Zumpano, 2009;Brown, 2000;Compton, Johnson, Kunkel, & Compton, 2006;Escobari & Jafarinejad, 2016;Hartzell, Kallberg, & Liu, 2008;Hartzell, Sun, & Titman, 2014;Ho & Tay, 2016;Huerta, Jackson, & Ngo, 2015;Larson, 2005;C. Lee, Chien, & Lin, 2012;Liow & Addae-dapaah, 2010;Lu, Chen, & Liao, 2014;Olanrele, Said, & Daud, 2014;Pellerin et al, 2013;Quek & Ong, 2008;San, Heng, & Pong, 2011;Yung, Li, & Jian, 2017), with USA market is the most studied so far, which is not surprising because USA REITs market is the mature one in the world. One example is a study by (Brown, 2000) found that mortgage REITs that financed real estate investment using financial leverage had deeper negative returns compared to equity REITs that financed the investment directly.…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 99%
“…One of the most common scope ofstudies in REITs performance is comparing performance of one or some REITs companies within one jurisdiction (Akinsomi, Ong, Ibrahim, & Newell, 2016;Aro-gordon, 2015;Asteriou & Beigazi, 2013;Bene, Anderson, & Zumpano, 2009;Brown, 2000;Compton, Johnson, Kunkel, & Compton, 2006;Escobari & Jafarinejad, 2016;Hartzell, Kallberg, & Liu, 2008;Hartzell, Sun, & Titman, 2014;Ho & Tay, 2016;Huerta, Jackson, & Ngo, 2015;Larson, 2005;C. Lee, Chien, & Lin, 2012;Liow & Addae-dapaah, 2010;Lu, Chen, & Liao, 2014;Olanrele, Said, & Daud, 2014;Pellerin et al, 2013;Quek & Ong, 2008;San, Heng, & Pong, 2011;Yung, Li, & Jian, 2017), with USA market is the most studied so far, which is not surprising because USA REITs market is the mature one in the world. One example is a study by (Brown, 2000) found that mortgage REITs that financed real estate investment using financial leverage had deeper negative returns compared to equity REITs that financed the investment directly.…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 99%